2005
DOI: 10.1016/j.physletb.2005.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Viscous dark energy and phantom evolution

Abstract: In order to study if the bulk viscosity may induce a big rip singularity on the flat FRW cosmologies, we investigate dissipative processes in the universe within the framework of the standard Eckart theory of relativistic irreversible thermodynamics, and in the full causal Israel–Stewart-Hiscock theory. We have found cosmological solutions which exhibit, under certain constraints, a big rip singularity. We show that the negative pressure generated by the bulk viscosity cannot avoid that the dark energy o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
119
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 13 publications
0
119
0
Order By: Relevance
“…Cataldo et al [35] have analysed the possibility of late acceleration, using Israel-Stewart formalism of bulk viscosity. In this work, the authors have used an ansatz for the Hubble parameter (inspired from the non-causal theory), and they have shown that the universe might have undergone a transition to the phantom behaviour leading to big-rip singularity.…”
Section: Introductionmentioning
confidence: 99%
“…Cataldo et al [35] have analysed the possibility of late acceleration, using Israel-Stewart formalism of bulk viscosity. In this work, the authors have used an ansatz for the Hubble parameter (inspired from the non-causal theory), and they have shown that the universe might have undergone a transition to the phantom behaviour leading to big-rip singularity.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the said limitations, because of simplicity of approach, Eckart theory has been adopted widely in the study of the accelerating universe filled with bulk viscous fluid (e.g. [60,62,63]). In the present work, we consider that in addition to the viscous EHRDE the universe also contains barotropic fluid, and consequently the Friedman equation and the corresponding equations of motion take the form [62]…”
Section: Eckart Approachmentioning
confidence: 99%
“…The dark energy phenomenon as an effect of the bulk viscosity in the cosmic medium has been first investigated in [48]. All these cited works are pioneer papers on the cosmological bulk viscosity, but it is also worth noting some recent applications of viscous fluids as candidates for dark matter [49], dark energy [50][51][52][53][54] or unified models [55][56][57][58][59][60], i.e., when a single substance plays the role of both dark matter and dark energy simultaneously. Indeed, it has been shown that for an appropriate viscosity coefficient, an accelerating cosmology can be achieved without the need of a cosmological constant [61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%